Massilibacterium senegalense gen. nov., sp. nov., a new bacterial genus isolated from the human gut. (March 2016) - Tidjani Alou, M.; Rathored, J.; Lagier, J.-C.; Khelaifia, S.; Labas, N.; Sokhna, C.; Diallo, A.; Raoult, D.; Dubourg, G.
Abstract: Massilibacterium senegalense gen. nov., sp. nov., strain mt8 T, is the type strain of Massilibacterium gen. nov., a new genus within the Bacillaceae family. This Gram-negative facultative anaerobic rod was isolated from the gut microbiota of a severely malnourished boy. Its phenotypic description is hereby presented with a complete annotation of its genome sequence. This genome is 5 697 950 bp long and contains 5615 protein-coding genes and 178 RNA genes, among which are 40 rRNA genes.